Front entrance of the Mahakal Temple complex - Temples of India Project Team (Jio Institute, 2024)
The front entrance (towards the west), possibly the original entry point in earlier times, is now locked with a metal gate which seems to have not been in regular use. There is a flight of steps which leads to the temple complex. Presently to facilitate the needs of the temple and devotees, a water tank is placed on one side of the entrance and the other side has a broken fragment of a pillar bracket.